The Description of Infectious Waste Management by Nurses Stationed at Inpatient Room of Arifin Achmad General Hospital of Riau Province - Dhea Putri Primadana Arum (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2021)
Hospital activities produce various kinds of hospital waste, one of which is infectious waste. Infectious waste management that is not good can cause health and environmental problems. This study aims to see an overview of infectious waste management by nurses in class III inpatient rooms (Dahlia, Edelweis, Kenanga, Krisan) Arifin Achmad Regional General Hospital, Riau Province. This study uses a simple descriptive design with the number of respondents 66 nurses using a total sampling technique. The data collection method in this study used a questionnaire. The analysis used is univariate analysis. The results of this study explained that as many as 48 nurses carried out infectious waste management well (72.7%). a total of 50 nurses have good knowledge of waste management (75.8%). The type of infectious waste in the treatment room is the majority of waste contaminated with patients in the isolation ward such as gauze, swab bandages, and other contaminated waste. a total of 50 nurses performed the waste sorting method well (75.8%) and 51 nurses performed the waste collection method well (77.3%). Overall, the nurses in the ward have performed the infectious waste management well. This research is expected so that nurses can further improve the quality of waste management in the inpatient room so that it will be even better in the future. Keywords: Infectious waste; Waste management;Nurses